Effect of electron beam irradiation on PMMA/ENR 50/LiCF3SO3 electrolyte / Nur Aziati Tahar @ Yusoff - Tahar @ Yusoff, Nur Aziati (2010)
Thin, transparent and flexible freestanding films of poly (methyl methacrylate) (PMMA)/ 50% epoxidised natural rubber (ENR 50) blends were obtained in this study. However, the films obtained were not homogenous in which phase separations were observed on the surface of the films. The in-homogeneity of the blends were confirmed from their optical micrographs by the presence of black patches of highly viscous of ENR 50 that unable to enter into PMMA phase. The inhomogeneity of the blends were further confirmed by the presence of two Tgs in their differential scanning calorimetry (DSC) thermograms. Therefore, the films were irradiated with electron beam irradiation at 0, 10, 20 and 30 kGy of irradiation doses in order to improve the homogeneity of the films. Physically, the homogeneity of the films were slightly improved after irradiation. From the optical micrograph, the homogeneity of the blend was improved when it was irradiated up to 20 kGy of irradiation dose in which the presence of black patches of highly viscous phase of ENR 50 was almost diminishing. This can be further confirmed from its DSC thermogram in which the distance of the two glass transition temperature, Tgs were almost merging. From the Fourier Transform Infra-Red (FTIR) analysis, this system exhibited the lowest intensity of C=O, O-CH3 and C-O-C bands indicating an increased in the interaction of the polymers, hence giving a more stable film which has been confirmed from their thermo gravimetric (TG) analysis. However, above 20 kGy of irradiation dose, the black patches of highly viscous phase of ENR 50 were observed again. This was probably due to the reformation of interchain cross-linking that increased the viscosity of the polymer hence limits its mobility to enter into PMMA phase. This 20 kGy irradiated system exhibited the highest ionic conductivity of 1.79 x 10-7 S/cm at room temperature and the lowest activation energy, Ea, when 0.2 g of lithium triflate (LiCF3SO3) salt was added into the system. From its FTIR analysis, it was exhibited the highest intensity of v(SO3) indicating the presence of the highest number of free lithium ion due to the formation of a less viscous phase of ENR 50. From its optical micrograph, it showed that the LiCF3SO3 salt was more soluble compared to the other irradiated system. However, no freestanding film can be obtained when more than 0.3 g of LiCF3SO3 salt was added into the system due to the formation of salt congestion. All the irradiated electrolyte systems were found to obey the Arrhenius rule in which the transportation of ions were via ion hopping.